In vitro evaluation of dental pulp stem cells for sciatic nerve regeneration: foundations for future in vivo applications - Lopes, Bruna; Sousa, Ana Catarina; Sousa, Patrícia; de Sousa Moreira, Alícia; Coelho, André Filipe; Atayde, Luís; Salgado, António J.; Geuna, Stefano; Alvites, Rui; Maurício, Ana Colette (Frontiers in Cell and Developmental Biology, 2025)
IntroductionPeripheral nerve injuries, resulting from trauma or medical interventions, present significant clinical challenges due to their severe physiological and functional impacts. Despite various therapeutic approaches, optimal methods for promoting nerve regeneration remain difficult to obtain. This study is a preliminary step towards the future use of chitosan nerve guide conduits combined with human dental pulp stem cells and their conditioned media to promote nerve regrowth in a rat model with severe sciatic nerve damage.MethodsPreliminary characterization of conditioned medium from human dental pulp stem cells identified key regenerative biomarkers using a Multiplexing LASER Bead analysis. The human dental pulp stem cells’ cytocompatibility with Reaxon® chitosan biomaterial was confirmed through viability and metabolic assays in a PrestoBlue assay, along with scanning electron microscopy and energy-dispersive X-ray spectroscopy analyses.ResultsThese in vitro assessments validated the therapeutic potential of the combinations for nerve regeneration.DiscussionFuture in vivo experiments will involve applying these combinations in a rat model, with functional assessments to evaluate efficacy. This research aims to establish human dental pulp stem cells and nerve guide conduits as viable treatments for peripheral nerve injury, offering promising directions for clinical applications.